2022
DOI: 10.1021/jacs.2c11341
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Helical Self-Assembly of Atomically Precise Nanoclusters

Abstract: The construction of helical nanosized superstructures has long been a challenging pursuit, and little has been achieved in terms of atomic-level manipulation. Herein, intercluster hierarchical triple-helical structures were presented from all-thiol-stabilized Au6Cu6(4-MeOBT)12 nanoclusters by investigating their structures from both molecular and supramolecular aspects. Based on the atomically precise structure, the mechanism of intercluster assembly was elucidated, and the results indicated an intracluster ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 54 publications
0
27
1
Order By: Relevance
“…Then, such giant superclusters could further act as TBUs for assembling four single‐crystal superstructures. Unlike that the BUs were normally unisolable and at the same hierarchy level in previously reported superstructures, [7f, 9e, 11a] herein multi‐level BUs are isolable and can coexist in one single‐crystal structure. Thus, hierarchical assembly, as well as the evolution of superstructures from the one with coexisting isolable SBUs and TBUs to 3D assemblies of TBUs, is clearly demonstrated.…”
Section: Figurecontrasting
confidence: 61%
“…Then, such giant superclusters could further act as TBUs for assembling four single‐crystal superstructures. Unlike that the BUs were normally unisolable and at the same hierarchy level in previously reported superstructures, [7f, 9e, 11a] herein multi‐level BUs are isolable and can coexist in one single‐crystal structure. Thus, hierarchical assembly, as well as the evolution of superstructures from the one with coexisting isolable SBUs and TBUs to 3D assemblies of TBUs, is clearly demonstrated.…”
Section: Figurecontrasting
confidence: 61%
“…Indeed, both intramolecular and intermolecular interactions could restrict the vibration/rotation of cluster molecules and further improve their molecular properties. [57][58][59][60][61] The intermolecular interactions (such as C-H⋯F, C-H⋯π, π⋯π) were widely discovered in nanoclusters, while the study of the restriction of intramolecular rotations was insufficient in metal nanoclusters. In this work, we demonstrated that ligand engineering could be an efficient surface control strategy for activating the intra-/inter-molecular interactions of metal nanoclusters, achieving the functionalization of cluster-based nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…1–10 The monodisperse sizes, precise compositions, and accurate configurations of metal nanoclusters make them good templates for obtaining insights into the relationship between structures and properties at the atomic level, which in turn promotes the rational construction of new nanoclusters with customized performances. 11–18…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The monodisperse sizes, precise compositions, and accurate configurations of metal nanoclusters make them good templates for obtaining insights into the relationship between structures and properties at the atomic level, which in turn promotes the rational construction of new nanoclusters with customized performances. [11][12][13][14][15][16][17][18] For efficiently controlling the construction and compositions of nanoclusters at the atomic level to tune their properties, an alloying strategy for the manipulation of metal composition and a ligand-engineering strategy for the regu-lation of the surface structure have often been reported. [19][20][21][22][23][24] Asymmetrically doping a platinum atom into Au 38 can change its electron configuration and reactivity during electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%